TEACHING ENGLISH AT THE INSTITUTE OF ARCHITECTURE - Axmedova Buvsara Majidovna (Scholar Express Journal, 2021)
This paper examines how modern technology can be used to teach a foreign language at a non-linguistic university
Keywords: educational opportunities; Innovation; methodology; Professional tasks